Astrocyte-secreted factors modulate synaptic protein synthesis as revealed by puromycin labeling of isolated synaptosomes - de la Cruz-Gambra, Aida; Baleriola, Jimena (Frontiers in Molecular Neuroscience, 2025)
The synaptic proteome can be shaped by proteins transported from the neuronal soma and/or by mRNAs that are delivered to synapses where proteins are locally synthesized. This last mechanism is known as local translation. Local translation has been extensively studied in neurons in physiological conditions and, more recently, in neurological disorders, in which local transcriptomes and translatomes become dysregulated. It is widely believed that in neurons, the main source of localized transcripts is the neuronal soma and that localized translation is primarily regulated by the neuron itself. However, we wondered whether glial cells, especially astrocytes, could contribute to the modulation of synaptic local protein synthesis. To address this question, we compared levels of proteins produced in synaptic compartments in neuronal and neuron–astrocyte co-cultures using modified Boyden chambers or astrocyte-conditioned medium. We developed a methodology to measure local protein synthesis by puromycin labeling of isolated synaptosomes devoid of somatic input. Our results show that synaptic local translation is enhanced or retained when neurons are cultured in the presence of astrocytes and in response to astrocyte-conditioned medium. Puromycin labeling coupled with proximity ligation identified Rpl26 as one of the proteins whose local synthesis is regulated by astrocyte-secreted factors. Our results thus unravel the contribution of glia to synaptic protein synthesis and point to a previously unexplored extra layer of complexity in the regulation of local translation in neurons.